Neofiscalin A and fiscalin C are potential novel indole alkaloid alternatives for the treatment of multidrug-resistant Gram-positive bacterial infections - Bessa, Lucinda J. (2017)
Ten indole alkaloids were obtained from the marine sponge-associated fungus Neosartorya siamensis KUFA 0017. We studied the antimicrobial properties of these and of three other compounds previously isolated from the soil fungus N. siamensis KUFC 6349. Only neofiscalin A showed antimicrobial activity against Gram-positive bacteria, including methicillin-resistant Staphylococcus aureus (MRSA) and vancomycin-resistant Enterococcus faecalis (VRE); with a minimum inhibitory concentration (MIC) of 8 μg mL(-1) against both strains. Another compound, fiscalin C, presented synergistic activity against MRSA when combined with oxacillin, although alone showed no antibacterial effect. Moreover, neofiscalin A, when present at sub-MICs, hampered the ability of both MRSA and VRE strains to form a biofilm. Additionally, the biofilm inhibitory concentration values of neofiscalin A against the MRSA and VRE isolates were 96 and 80 μg mL(-1), respectively. At a concentration of 200 μg mL(-1), neofiscalin A was able to reduce the metabolic activity of the biofilms by ∼50%. One important fact is that our results also showed that neofiscalin A had no cytotoxicity against a human brain capillary endothelial cell line.